Nonlocal Impulsive Cauchy Problems for Evolution Equations. (25th November 2010) - Liang, Jin; Fan, Zhenbin
Abstract : Of concern is the existence of solutions to nonlocal impulsive Cauchy problems for evolution equations. Combining the techniques of operator semigroups, approximate solutions, noncompact measures and the fixed point theory, new existence theorems are obtained, which generalize and improve some previous results since neither the Lipschitz continuity nor compactness assumption on the impulsive functions is required. An application to partial differential equations is also presented.